Stolen - Simon West; Cage, Nicolas; Josh Lucas; Huston, Danny; Malin, Akerman; Sami Gayle (USA Millennium Films, 2012)
Will Montgomery (Nicolas Cage) is a master thief who after being double-crossed in a heist gone awry is sent to prison for 8 years. Upon his release he's ready to leave his criminal past behind and try to rebuild a relationship with his estranged daughter Allison. The FBI and his old cohorts believe that he hid the loot from the last heist 8 years ago, $10 Million in Bonds. To get his hands on it, his old partner Vincent kidnaps Allison and demands the entire $ 10 Million as ransom.
Language: English Subtitle: Turkish
Keywords: Action; Drama; Thriller